Efficacy and safety of montelukast sodium combined with fluticasone in the treatment of adult bronchial asthma: A protocol for systematic review and meta-analysis. Issue 52 (24th December 2020) - Luo, Huiling; Han, Hongmei; Liu, Xiaoli; Liu, Qin
Abstract: Background: Bronchial asthma (BA) is a chronic airway inflammatory disease with reversible airflow limitation as the main clinical manifestations, such as wheezing, cough, shortness of breath, chest tightness, etc, mediated by a variety of inflammatory cells, which can be recurrent. Clinical can improve symptoms, but cannot be cured; glucocorticoid is the most important first-line medication. Clinical practice has shown that montelukast sodium combined with fluticasone in the treatment of adult BA can improve clinical efficacy and reduce adverse reactions. The purpose of this study is to systematically study the efficacy and safety of montelukast sodium combined with fluticasone in the treatment of adult BA. Methods: The Chinese databases (CNKI, VIP, Wanfang, Chinese Biomedical Database) and English databases (PubMed, the Cochrane Library, Embase, Web of Science) were searched by computer, for the randomized controlled clinical studies of montelukast sodium combined with fluticasone in the treatment of adult BA from establishment of database to October 2020. Two researchers independently extracted the relevant data and evaluated the quality of the literatures, and used RevMan5.3 software to conduct meta-analyze of the included literatures. Results: This study assessed the efficacy and safety of montelukast sodium combined with fluticasone in the treatment of adult BA through total effective rate, pulmonary function (FEV1, FVC, PEF, FEV1/FVC), and adverse reactions. Conclusion: This study will provide reliable evidence-based evidence for the clinical application of montelukast sodium combined with fluticasone in the treatment of adult BA. OSF Registration number: DOI 10.17605/OSF.IO/CKQFM